370 THE INFLUENCE OF ADVERSE DONOR FACTORS AFFECTING OUTCOME OF PEDIATRIC HEART TRANSPLANTATION: THE MARGINAL DONOR ALLOGRAFT. Issue 1 (1st January 2007) - Yao, W.; Saran, M.; Laks, H.; Gjertson, D.; Odim, J.
Abstract : Background: We sought to examine the influence of various marginal donor criteria on pediatric heart transplantation outcome. Methods: We reviewed the medical records of 236 pediatric heart transplants performed in 213 patients from 1984 through 2006 at UCLA. Recipients were grouped into four (0, 1, 2, and > 3 marginal factors) based on the number of donor marginal criteria. A marginal donor allograft was defined by at least one of the following criteria: hx of cardiac arrest, LVEF < 50%, positive hepatitis B or C serology, dopamine > 10 μg/kg/min, gender mismatch (female donor), age > 34 years, allograft ischemia time > 6 hours, and donor-recipient weight ratio < 0.8 > 2. Study end points were actuarial survival and freedom from rejection. A Cox proportional hazards model was used for statistical analysis. Results: In addition, TCAD-free survival is significantly greater at 3 years for low-risk patients receiving a nonmarginal donor (95 ± 3%) compared with those receiving a donor heart with 2+ marginal factors (70 ± 11%, p value .01). There was no statistical difference in TCAD-free survival among high-risk patients. Conclusions: There was worse outcome associated with patient survival between patients receiving hearts with 3+ marginal factors compared with those receiving 0 marginal factors. In addition, there is a higher incidence of TCAD among low-risk recipients when receiving a heart with 2+ marginal factors.